Adjustments of mathematical models for drying maize seeds on cobs - Neves, Eletisanda das; Geraldi, Claudinéia Aparecida Queli; Franz, Gabriela Maria (Scientific Electronic Archives, 2024)
The present study aimed to select the mathematical models that best fit the drying kinetics of maize seeds on the cob. A 50- and 150-cm maize layer was used in the dryer for four airflows: 5. 10, 15 and 20 m 3.min -1.t -1 was used for stationary drying. The ears were dried in four prototypes of stationary perforated false-bottom dryers with a diameter of 0.92 m, height of 1 m and axial fan. The temperature of the drying air was controlled at the base of the dryer chamber using a thermostat. The mathematical models were analyzed via linear regression. The model of Page and Handerson & Pabis was used. The results showed that the Page model was more satisfactory for predicting the data for the 50 cm layer of ears than the Henderson & Pabis model was for predicting the data for the 150 cm layer. However, both models can be used to represent the drying phenomenon of maize seeds on cobs